Multi-objective Tabu Search 2: first technical report - Tsotskas, Christos; Kipouros, Timoleon; Savill, Mark A. (Cranfield University, 2015)
The purpose of this document is to describe Multi-Objective Tabu Search 2 (MOTS2), which is a native mutli-objective optimiser. It has been developed to tackle a variety of real-world problems of engineering interest. The design and implementation are presented, followed by verification, validation and user instructions. At a glance, it involves introduction to the algorithm, explains configuration settings and structure, and results interpretation. Then, the optimiser is tested against a series of mathematical test functions in order to verify its functionality. The main goal is to demonstrate and assess the performance and applicability of the optimiser. The next step is to use MOTS2 on a real-world case, where the performance of optimising a 2D airfoil is validated and illustrated.